2013
DOI: 10.5194/npg-20-189-2013
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear hydrodynamics in a Mediterranean lagoon

Abstract: The paper addresses the application of the nonlinear hydrodynamics model (RANS (Reynolds-averaged Navier–Stokes) equations) in a wide semi-enclosed Mediterranean lagoon (Berre lagoon), considering three natural forcing functions, i.e., sea tide propagating through a long narrow channel, wind and runoff. Main attention is focused to characteristic velocities (at free surface and bottom) and to free surface elevation associated to each of these three mechanisms, with special attention to the nearshore areas (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 17 publications
2
15
0
5
Order By: Relevance
“…Difference scheme. The difference method was constructed to approximate the developed model [5][6]. Comparison of simulation results with full-scale data showed that the calculation error for the proposed model is 10-15% [1].…”
Section: Vol 2 № 2 / 2018mentioning
confidence: 99%
“…Difference scheme. The difference method was constructed to approximate the developed model [5][6]. Comparison of simulation results with full-scale data showed that the calculation error for the proposed model is 10-15% [1].…”
Section: Vol 2 № 2 / 2018mentioning
confidence: 99%
“…Let us consider the equation of sediment transport according to the [10][11][12][13][14][15]: Further, for simplicity, the equation (1) was considered…”
Section: The Formulation Of the Nonlinear Initial-boundary Value Probmentioning
confidence: 99%
“…On the basis of the constructed algorithms were developed software intended for modeling of sediment transport in shallow waters [2][3]. The developed software, used to calculate two-dimensional velocity vector of the flow of the water environment, takes into account the turbulent exchange, the geometry of the seabed, wind currents and friction on the bottom.…”
Section: Mathematical Model Of Sediment Transportmentioning
confidence: 99%
“…The equations of the process of sediment transport [1][2][3][4][5] can be written in the following form:…”
Section: Mathematical Model Of Sediment Transportmentioning
confidence: 99%
See 1 more Smart Citation